PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF SISTEM TATA SURYA BERBASIS VIRTUAL REALITY BOX 360˚ UNTUK PLATFORM ANDROID - teguh pradana; Arnas Rama Apriadji (STMIK YADIKA BANGIL, 2021)
Abstract: Instructional media is an important role in overcoming the difficulties of the learning process in schools. One of the most useful lessons in school to find out what is beyond Earth or space is about the solar system. As we already know learning the solar system is very difficult for us to imagine even though there are already media books to explain images of the solar system but students' imaginations are still unable to visualize properly because the human senses that cannot measure dimensions are also due to inaccessible distances by humans. Consequently learning outcomes are not optimal because they depend on the imagination of students. A form of learning media that can simplify the student visualization process is a 3d-based computer media. one of the techniques that support 3D visualization is virtual reality. Which media can help the learning process to be interesting and more efficient.Keywords: Visualization, Virtual Reality, Solar System